2012
DOI: 10.1093/ejcts/ezs016
|View full text |Cite
|
Sign up to set email alerts
|

Arterial switch in the first hours of life: no need for Rashkind septostomy?

Abstract: ASO for D-TGA in the first hours of life is a good option for the treatment of critically ill neonates with metabolic disorders. In our experience, there is no need for the Rashkind procedure to stabilize the patient before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…12,13 Nevvazhay et al reported eight patients with favorable outcomes after ASO in the first 24 hours of life as an alternative to septostomy but did not provide results of a comparison group. 12 Chasovskyi et al demonstrated the feasibility of using umbilical cord blood in 21 patients undergoing ASO at a mean age of 11 hours. 13 Compared to 40 control patients with a mean age at ASO of 7.7 days, the early repair group had a lower total LOS.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Nevvazhay et al reported eight patients with favorable outcomes after ASO in the first 24 hours of life as an alternative to septostomy but did not provide results of a comparison group. 12 Chasovskyi et al demonstrated the feasibility of using umbilical cord blood in 21 patients undergoing ASO at a mean age of 11 hours. 13 Compared to 40 control patients with a mean age at ASO of 7.7 days, the early repair group had a lower total LOS.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] In these diseases signs of PFO restriction should alert the clinician and require urgent Rashkind procedure or anticipation of surgical correction/palliation. [2][3][4][5][6][7] Foramen ovale is easily evaluated by echocardiography.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] In these diseases signs of PFO restriction should alert the clinician and require urgent Rashkind procedure or anticipation of surgical correction/palliation. [2][3][4][5][6][7] Foramen ovale is easily evaluated by echocardiography. [1][2][3][4][5][6][7] Echocardiography is also commonly employed to guide the Rashkind procedure as well as to evaluate its result.…”
mentioning
confidence: 99%
See 2 more Smart Citations